A Neutrosophic Technique Based Efficient Routing Protocol For MANET Based On Its Energy And Distance - Said Broumi; Mohamed Talea; Assia Bakali; Florentin Smarandache; Prem Kumar Singh; Mullai Murugappan; V. Venkateswara Rao (Neutrosophic Sets and Systems, 2019)
In the last decade, characterizing the energy in MANET based on its acceptation, rejection and uncertain part is addressed as one of the major issues by the researchers. An efficient energy routing protocol for MANET is another issue. To resolve these issues current paper focuses on utilizing the properties of neutrosophic technique. The essential idea of the protocol is to choose an energy efficient route with respect to neutrosophic technique. In this neutrosophic set, we have three components such as (T, I, F). Each parameter such as energy and distance is taken from these neutrosophic sets to determine the efficient energy route in MANET. After taking a brief survey about energy efficient routing for MANET using various methods, we are trying to implement the neutrosophic set technique to find the efficient energy route for MANET which provides the better energy route in uncertain situations. The comparative analysis between vague set MANET and neutrosophic MANET for the values of energy functions and distance functions is done by using Matlab and the result is discussed graphically.